2013
DOI: 10.1371/journal.pone.0075909
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Spotted Wilt Virus Benefits a Non-Vector Arthropod, Tetranychus Urticae, by Modulating Different Plant Responses in Tomato

Abstract: The interaction between plant viruses and non-vector arthropod herbivores is poorly understood. However, there is accumulating evidence that plant viruses can impact fitness of non-vector herbivores. In this study, we used oligonucleotide microarrays, phytohormone, and total free amino acid analyses to characterize the molecular mechanisms underlying the interaction between Tomato spotted wilt virus (TSWV) and a non-vector arthropod, twospotted spider mite ( Tetranychusurticae ), on tomato plants, Solanum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 48 publications
0
35
1
1
Order By: Relevance
“…Tomato plants inoculated with TSWV also results in the establishment of a compatible interaction, however the accumulation of phenolic compounds in this system has not yet been fully explored [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…Tomato plants inoculated with TSWV also results in the establishment of a compatible interaction, however the accumulation of phenolic compounds in this system has not yet been fully explored [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…Genes involved in cellular detoxification are also up-regulated, signalling for the production of antioxidant enzymes such as peroxidases, catalase and superoxide dismutase (Grinberg et al 2005;Nachappa et al 2013). Through a combined metabolomics and transcriptomics approach, Kant (2004) showed that one day after infestation by TSSM on tomato leaves, direct defence responses (such as proteinase inhibitor activity and transcription of genes involved in JA-, SA-, and ethyleneregulated defences) had already been activated.…”
Section: Molecular and Physiological Changes Caused By Phytophagous Mmentioning
confidence: 99%
“…The primary metabolism of infested plants is disturbed, specifically changing the metabolism of amino acids and carbohydrates, as well as changing the hydric potential of their cells. Nutrient transportation can also be interrupted to hinder feeding, but this is not always effective (Nachappa et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Gaseous phytohormones, such as ethylene and a series of terpenes, as well as jasmonic acid (JA) and salicylic acid (SA) 14 are released by plants and regulate several defense signaling mechanisms 12 . Genes involved in cellular detoxification may also be up-regulated, signaling for the production of antioxidant enzymes 15 .…”
Section: Introductionmentioning
confidence: 99%